Issues and trends in technology and human interaction - Stahl, Bernd Carsten 1968- (Gale virtual reference library, 2007)
"This book provides a wide range of interesting and novel approaches to the relationship between technology and humans. It can be used for teaching as well as for research purposes; it contains insights that are of relevance for social and organizational use of information and communications technology"--Provided by publisher.